Flipped Project-Based Learning Model in Creative Writing Class: How Do Students Need It? - Harris Effendi Thahar; Afdetis Mana, Lira Hayu; Atmazaki; Samsudin, Nurul Haniza (International Journal of Language Pedagogy, 2024)
Student needs for each course are different. Implementations that do not meet the needs will cause problems in the learning process. This study aims to analyze the characteristics of materials to be used in creative writing classes, especially while learning opinion writing that meets the students' needs of learning materials. This research is a quantitative descriptive study. Using purposive sampling technique, 38 of all students of the PGRI University of West Sumatra in the Indonesian Language and Literature Education Study Program, participated in this study. The students were asked to respond to an online questionnaire investigating their situation in the creative writing class, their needs and difficulties in learning materials about opinion writing as one of subtopics in the creative writing course. This research provides insights to design a Flipped Project Based Learning model using an e-learning platform. The results revealed that with the conventional learning, some students were less motivated and creative, so it is necessary to provide learning materials that can encourage all students' active participation and writing creativity without exception . Besides, the students need a complete and systematic set of learning materials about the concept of opinion writing that allows them to customize the topics and ideas for writing opinions, along with lecturer guidance in understanding the concept of writing the opinions. Additionally, the materials should be able to help them deal with their difficulties in determining ideas and the title of the opinion essay.